PEMANFAATAN LIMBAH INDUSTRI ARANG SEBAGAI BRIKET RAMAH LINGKUNGAN DENGAN TTG ALAT PRESSING BRIKET - Avriel Syanu; Visto Duan Apriano; Adinda Atsiil Nabila; Ainur Rizqi; Adam Fatahilah; Rizki Yudha Satria; Mohammad Rizal Syahputra; Nabilla Nur Anisyah; Robiah Al Adawiyah; Zulfaa Fuad Syani; Helda Wika Amini (Jurnal Abdi Insani, 2026)
Lojejer Village, Wuluhan, Jember, is an area with home-based charcoal industries that operate daily. The charcoal production generates waste such as charcoal ash, which is unutilized and released into the environment. This problem presents an opportunity to increase the economic value of charcoal ash waste by processing it into eco-friendly briquettes with higher heat and economic value. Promahadesa Libera from the University of Jember has developed an Appropriate Technology (AT) briquette-pressing machine to enhance briquette production efficiency. Promahadesa Libera also conducted socialization activities through discussion sessions, machine donation, and direct mentoring for the community by forming a briquette production team in collaboration with local residents. These activities received highly enthusiastic responses from the local community and increased public understanding of AT and its potential to transform charcoal industry waste into valuable products that can support the economic development of the local community.